Intentional Homicides and Inequality in Guayaquil: A Spatial Analysis in 2023 - Arce Bastidas, Rafael (Revista Universidad de Guayaquil, 2026)
Homicidal violence in urban environments constitutes a critical challenge in cities marked by socioeconomic inequality and territorial segregation. This study examines the geographical distribution of intentional homicides in Guayaquil during 2023 using Geographic Information Systems (GIS) and spatial analysis techniques, specifically the Kernel Density method and Global Moran's Index. The hypothesis posits that homicides tend to concentrate in areas with greater levels of economic and social inequality, evidencing the influence of structural factors on the distribution of urban violence. The results confirm this hypothesis, revealing a marked concentration of homicides in the northern and southern zones of the city, inhabited by low and lower-middle income populations. Guayaquil registered a rate of 89.87 homicides per 100,000 inhabitants, considered epidemic according to the United Nations threshold, with an 884.3% increase compared to 2014. Significant positive spatial autocorrelation (Moran's Index ≈ 0.45, p < 0.05) confirms that homicides cluster persistently in certain urban sectors. The analysis revealed the high prevalence of firearm use and a majority impact on individuals aged between 25 and 30 years. These findings demonstrate that the spatial pattern of violence is not random but rather the result of structural inequalities and territorial segregation, supporting theories of social exclusion, anomie, and the production of urban space. The study highlights the urgent need for comprehensive public policies that articulate urban planning, social inclusion, and citizen security, whilst demonstrating the utility of geospatial analysis for guiding territorialized interventions.
Keywords: Guayaquil; Homicides; Socioeconomic Inequality; GIS; Structural Violence